Morpho-physiological responses in wheat (Triticum aestivum L) influenced by normal and water stress conditions - Piar Ali Shar; Akhtar Hussain Shar; Shabana Memon; Ayaz Ali Soomro; Saleem Ahmed Naich; Nadir Ali Rind; Asadullah Laghari; Khalid Hussain Rind; Parkash Meghwar; Sohail Ahmed Otho (Journal of Agriculture and Applied Biology, 2021)
Drought is a disaster around the world accumulating salt and erosion in lands. Presently, a research was conducted to determine the mor-pho-physiological response in bread wheat under normal and stress irrigations. This experiment was conducted at the experimental field of Sindh Agriculture University, Tandojam, Hyderabad, Pakistan, for two consecutive years during the Rabi season of the year 2011-12 and 2012-13. Stress was imposed by withholding irrigations at three dif-ferent growth stages of the plant, i.e. T1: normal irrigations applied, T2: stress at tillering stage, and T3: stress at the booting stage. The progenies Sarsabz x Khirman and Sarsabz x TD-1 contributed the highest heritability% (81.0% and 85.5%) for osmotic potential (-MPa) at stress at booting stage. For grain yield spike-1(g), the progeny Kiran-95 x Khirman showed maximum heritability as 84.37 in T3. However, the progeny TD-1 x Imdad proved to be the best combiner progeny indicating highest heritability percentage (91.0%) among the progenies for grain yield at booting stress.